Winning Ways With Hydrogen Sulphide on the Namibian Shelf - Currie, Bronwen; Utne-Palm, Anne Christine; Salvanes, Anne Gro Vea (Frontiers in Marine Science, 2018)
The shelf sediments off Namibia are some of the most unusual and extreme marine habitats because of their extremely high hydrogen sulphide concentrations. High surface productivity of the northern Benguela upwelling system provides benthic life with so much carbon that biotic processes must rely on innovative mechanisms to cope with perennial anoxia and toxic hydrogen sulphide. Bottom dwelling communities are forced to adapt lifestyles to deal physically, physiologically and behaviourally with these stressful conditions. The upside of hydrogen sulphide is that it fuels extensive mats of large sulphide-oxidizing bacteria on the seabed, which create detoxified habitat niches and food for the animals living there. The threat of hypoxic stress exacerbated by hydrogen sulphide is largely overcome in the water column by microbes that detoxify sulphide, allowing animals in the upper water layers to thrive in this productive upwelling area. The bearded goby Sufflogobius bibarbatus is a cornerstone species that successfully couples the inhospitable benthic environment with the pelagic. Benthic studies have as yet not characterized the sulphidic shelf communities, which have the potential to uncover biotic adaptations to toxic sulphide. This ancient shelf upwelling system has long operated under hypoxic pressure, balancing always the abundance of particulate food against oxygen limitation and hydrogen sulphide toxicity. Challenges faced by this unique system could include environmental changes related to climate change, or man-made physical disturbances of the anoxic, sulphide-rich seabed sediments.